Optical Microfiber Sensing of Adulterated Honey - Irawati, Ninik; Isa, Naimah Mat; Mohamed, Auji Fatin; Rahman, Husna Abdul; Harun, Sulaiman Wadi; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2017)
A simple microfiber sensor is proposed and demonstrated for the detection of honey adulteration. The sensor uses a polymer microfiber and a silica microfiber probe. The polymer microfiber is fabricated using a direct drawing method from molten poly (methyl methacrylate) and has a waist of 2.3μm and a length of 3 mm, whereas the silica microfiber is fabricated using the flame brushing technique and has a waist of 2.5μm and a length of 3 mm. The probe is immersed in a honey adulteration solution and senses the relative honey adulteration using intensity modulation technique. Six types of honey samples were adulterated with different percentages of glucose. As honey adulteration varies from 1% to 6%, the transmission power of the polymer microfiber decreases from 3.51 to 1.15μ W with a sensitivity of 0.49μW% and a linearity of more than 96.97%. Meanwhile, the transmission power of the silica microfiber decreases from 14 to 7μW with a sensitivity of 1.37μ W% and a linearity of more than 96.80%.